Diterpenoid Alkaloids from Delphinium ajacis and Their Anti-RSV Activities - Yang, Li; Zhang, Yu-Bo; Zhuang, Ling; Li, Tao; Chen, Neng-Hua; Wu, Zhong-Nan; Li, Pan; Li, Yao-Lan; Wang, Guo-Cai (Planta Medica, 2017)
Five new diterpenoid alkaloids, ajacisines A–E (1–5), were isolated from Delphinium ajacis, along with seven known alkaloids (6–12). On the basis of their spectral data (IR, UV, HR-ESI-MS, 1D and 2D NMR) and chemical properties, the structures of compounds 1–12 were identified. All isolated compounds were evaluated for their in vitro antiviral activities against respiratory syncytial virus, and compounds 3–5 and 8 exhibited moderate to weak effects with IC50 values of 75.2 ± 1.1, 35.1 ± 0.6, 10.1 ± 0.3, and 50.2 ± 0.5 µM, respectively.
Keywords: Delphinium ajacis; Ranunculaceae; diterpenoid alkaloid; anti-RSV activity